Superconducting Properties of Sol-Gel Derived Bi(Pb)-Sr-Ca-Cu-O System - Al-Khawaldeh, Saleh Ayed Ahmad (1998)
The Bi₂₋ᵪPbᵪSr₂Ca₂Cu₃Oᵧ (2223) superconductor, has been prepared by sol-gel technique, using metal acetate precursors. Room temperature hydrolysis followed by polycondensation and heating yielded a transparent blue gel. The key to successful gel formation was due to a firm control of the pH of the solution. It was required to maintain the pH at 5.5 throughout the sol to gelation process. The decomposition of the polyhydroxyl metal complex to amorphous gel was found to be completed at temperatures in the range of 200 to 250'C producing submicron size particles. The amorphous gel transformed into crystalline powder at 600' C to 700' C. The effect of heat treatment as a function of sintering time and temperature have been also studied on Bi₂₋ᵪPbᵪSr₂Ca₂Cu₃Oᵧ system. The 2223 phase was observed in samples sintered at 8450 C for 48 h. The effect of the Pb doping at the bismuth lattice site have been studied in the Bi₂₋ᵪPbᵪSr₂Ca₂Cu₃Oᵧ ( x= 0.0, 0.4, 0.5 ) samples. Two samples doped with 20 and 25 mole % of Pb in the bismuth site yielded single phase sample with T, (R=O) above 102 K. Undoped sample had mixed phases (2212 and 2223). The study shows that the doped-sample with 25 mole % of Pb is the most suitable ratio that gives rise to the best superconducting properties. New procedure adopted in this work succeeded in getting good quality gel from carbonates, oxides and nitrates as the starting materials. The study shows that high-purity single-phase superconductor with T, (R=O) at 104 K was obtained from carbonate and oxide as starting materials. This value is comparable to that obtained from corresponding metal acetates.